Modelo conceitual das relações das tecnologias digitais da indústria 4.0 com a gestão da cadeia de suprimentos sustentável - Gomes, Leonildo Freitas (2023)
To help with the continuation of business competitiveness, new strategies and forms of management are adopted by organizations. With the growing importance of sustainable development, the concept of sustainability is being integrated into the supply chain, called Sustainable Supply Chain Management (GCSS). Companies face barriers to implementing sustainable practices, but Industry 4.0 digital technologies are establishing support for these practices. Industry 4.0 digital technologies have the potential to leverage and consolidate sustainability initiatives in supply chains, as it enables gains from the Triple Bottom Line (TBL), which is the sustainability tripod, for an action to be considered sustainable it needs to meet the TBL. This work aims to develop a conceptual model of the relationships between Industry 4.0 technologies in the GCSS. For this, a bibliometric and systematic review was carried out on the effects of Digital Technologies I4.0 (TDI4.0) in the GCSS and eight technologies addressed in the researched literature were found, and twenty-five sustainable gains, of which six social gains, ten gains economic and nine environmental gains. The model connected each identified gain with Industry 4.0 technologies, supported by the literature review. To verify the acceptance of the model, a questionnaire-type research instrument was used with specialists in Digital Technologies of Industry 4.0. Among the results found, IoT enables increased health and safety at work, reduces costs and waste. As a practical contribution, it enables the company to find out which technologies meet a certain sustainable gain and which needs to be improved, promoting sustainable practices and maintaining market competitiveness. As a theoretical contribution, I gathered articles on two relevant topics, providing research gaps. As a contribution to society, the use of the proposed map can contribute to the promotion of sustainable practices and makes it possible to achieve the goals established by regulatory bodies.